Cost of colorectal cancer by treatment type from different health economic perspectives: A systematic review. Issue 10 (October 2022) - Bhimani, Nazim; Wong, Geoffrey YM.; Molloy, Charles; Dieng, Mbathio; Hugh, Thomas J.
Abstract: Advancements in colorectal cancer treatment have substantially improved overall survival. However, the cost of treating colorectal cancer places a significant economic burden on populations and healthcare systems. It is accepted that costs and what a health system charges may differ. This study aims to understand the expenditure on colorectal cancer globally. Specifically, this paper systematically reviews the literature to estimate the direct costs of each component in treating colorectal cancer, including primary care, diagnostics, surgery, chemotherapy, radiotherapy, and follow-up. MEDLINE, EMBASE, Web of Science, Evidence-Based Medicine Reviews: National Health Service Economic Evaluation Database Guide, Econlit and grey literature from the January 1, 2000 to the February 1, 2020. The methodological quality of the included studies was assessed using the Evers' Consensus on Health Economic Criteria checklist. In total, 39, 489 records were retrieved, and after appropriate culling of non-relevant articles, 15 studies were included. Costs for treating colorectal cancer varied due to heterogeneity between different studies despite comparing similar clinical settings and study perspectives. Studies that presented an average cost per patient demonstrated that surgical costs ranged from 1, 149 to 34, 606, chemotherapy ranged from 1, 883 to 18, 021 and radiotherapy ranged from 2, 037 to 5, 347 in 2018 USD. Identifying these costs can impact health care budgets and guide policymakers in making informed decisions for the future.